Makna Kebebasan Pers Di Indonesia - Liando, Daud Markus (JURNAL ILMIAH SOCIETY, 2016)
This study reveals the meaning of freedom of the press in Indonesia using the approach of Agenda Setting Theory of Mc Combs and Shaw and Releases Social Responsibility Theory of Theodore Peterson, using qualitative research methods. The results showed press freedom being developed today is freedom of the press in the context of democratic development. Freedom to seek, manage and menayajikan news is now strongly felt by members of the press, but freedom must be accompanied by responsibility for news content. The press is one of the most instrumental agents of change in society changes. The press had a strong driving force that can bring the society towards the negative or reverse direction towards a better improvement. Journalists must improve quality by constantly, have a passion to improve the skills of the profession as a journalist. Freedom of the press has been followed by the media presence of their owners who have enough capital. It also influence the news content, in which journalistic work presented to the public can not be separated from the element alignments. Journalists who act independently, presents a true and accurate news without any interference whatsoever, including media owners have not fullyÂ  in Indonesia. Keywords: Press, Freedom of the Press